Perencanaan Peningkatan Produktivitas UMKM Berbasis Metode American Productivity Center (APC) Untuk Mengurangi Fluktuasi dan Memenuhi Target Kinerja - Sri Wahyuni, Rahayu; Chandrahadinata, Dody; Jianul Hayat, Encep (Jurnal Kalibrasi, 2025)
This study aims to measure productivity, identify causes of fluctuations, and formulate improvement strategies for garment MSMEs in Garut Regency. Data was collected from June to December 2024, covering input variables such as labor, materials, energy, and capital, as well as output variables such as production value in rupiah. The American Productivity Center (APC) method was used to calculate the Productivity Index (PI), Profitability Index (PI), and Price Improvement Index (PI) with a base period of June. The results show that the total productivity index ranges from 98.40% to 101.34%, with the highest value in August (labor IP 120.92%) and the lowest in September (88.72%). Gap analysis revealed the main causes of fluctuations, namely excess stock after Eid, lack of labor discipline, high employee turnover, and inefficient capital costs. The SWOT analysis resulted in productivity improvement strategies, including optimizing experienced labor, implementing incentive systems, flexible work scheduling, efficient raw material planning, increased online promotion, and developing distribution partnerships. This study provides practical contributions in the form of data-based strategy guidelines for garment MSMEs to achieve stable and sustainable productivity.